Ethnic relations in Malaysia 1930-40 - Wan Sulong, Wan Suhana (s.n, 2013)
The history of Malaya (later Malaysia) from 1930 to 1940 was marked by the growing tension between various ethnic groups. The influx of immigrant races, mainly the Chinese and Indian, posed a challenge to the Malaya as indigenous people of Malaya. Thus, this paper attempts to highlight issues related to ethnicity which dominated Malayan scene during that time the factors which influenced relations between various ethnicity the debates in various journals and newspapers on ethnic issues the roles of leaders from various ethnicities in shaping relations in Malaya